Aortic annulus elevation for aortic valve and root replacement. Issue 4 (24th January 2022) - Jahanyar, Jama; Mastrobuoni, Stefano; Munoz, Daniel E.; Aphram, Gaby; de Kerchove, Laurent; El Khoury, Gebrine
Abstract: Aortic valve and root replacements require an in‐depth understanding of the aortic root and annulus. Both structures can be asymmetric at times, and this needs to be recognized and taken into consideration when performing valve‐sparing operations or other root‐replacement procedures. Moreover, the geometry of the aortic annulus can be altered, and when performing an aortic root replacement this can distort the geometry of a neoaortic valve for instance, and lead to valve dysfunction, which is difficult to reverse. We are describing an altered aortic annulus, which required modification through annulus elevation before proceeding with aortic root replacement with a graft‐reinforced pulmonary‐autograft.